Sintering and properties of dense manganese-doped calcium phosphate bioceramics prepared using sol-gel derived nanopowders - Sopyan, Iis; Nawawi, Natasha Ahmad; Shah, Qasim Hussain; Ramesh, Singh; Tan, Chou Yong; Abd Shukor, Mohd Hamdi (Taylor & Francis, 2011)
Dense manganese-doped biphasic calcium phosphate (Mn-BCP) ceramics were fabricated via uniaxial pressing using the sol-gel derived powders. The compacted discs were sintered in ambient atmosphere with temperatures ranging from 800C to 1400C. Manganese (Mn) level was varied in the range of 0.6, 1.9, 4.3, and 11.9mol%, and its effect on physical and mechanical properties of the dense samples were investigated. All dense samples have been proved to show HA and -TCP phases only. Mn doping has shifted the onset of the sintering temperature of the BCP, leading to the improved densification of BCP ceramics. The relative density also increased with sintering temperature. Considerable grain growth has been observed for Mn-doped BCP samples when compared to the undoped BCP. Furthermore, 11.9mol% Mn-doped BCP dense samples showed the maximum hardness of 6.66GPa compared to 2.89 GPa for the undoped BCP. The incorporation of Mn was also found to be beneficial in enhancing the fracture toughness of BCP throughout the temperature range employed. This study has shown that Mn doping was effective in improving the sintering properties of BCP without affecting the phase stability.